Influence of Mesoscale Features on Mixed Layer Dynamics in the Arabian Sea. Issue 5 (25th May 2019) - Trott, Corinne B.; Subrahmanyam, Bulusu; Nyadjro, Ebenezer S.
Abstract: During the summer monsoon season from June through September, low‐level winds from the Findlater Jet induce strong mesoscale activity and seasonal deepening of the mixed layer. For the first time, we have investigated the impact of mesoscale features on the strong intraseasonal variability of the mixed layer depth in the Arabian Sea using simulations from a reanalysis version of the HYbrid Coordinate Ocean Model and the European Centre for Mid‐range Weather Forecasting ERA‐Interim product. We identify and track mesoscale eddies using an eddy‐tracking algorithm during strong and weak summer monsoon conditions to determine the importance of mesoscale features on mixed layer variability during strong and weak wind forcing. We identify frontal systems in the Arabian Sea and observe how they strengthen with depth throughout the summer monsoon season. To quantify the role of these features on mixed layer variability, we also explore the roles of wind forcing, evaporation, precipitation, significant wave heights, and surface heat fluxes on mixed layer variability. A mixed layer heat budget was computed in the Arabian Sea, finding a strong dominance of vertical advective entrainment followed by compensation by horizontal processes indicating strong mesoscale activity. Plain Language Summary: The uppermost layer of the ocean is full of dynamic features such as frontal systems and quasi‐circular circulations on the order of 10–100 km called eddies. These features actively redistribute waters throughout the oceanic surface layer in which temperature, salinity, and density is almost vertically uniform, referred to as the mixed layer. In the Arabian Sea, the mixed layer deepens twice seasonally: once in the boreal winter and once in the boreal summer. In the wintertime, cool air blows over the Arabian Sea and cools the surface, which then sinks and deepens the mixed layer. In the summer, strong southwesterly winds deepen the mixed layer and provide conditions conducive to strong eddying and frontal development. In this paper, we compare the distribution of these mesoscale features under strong (weak) wind forcing associated with heavy (scanty) rainfall conditions and referred to as strong (weak) monsoon conditions. We find through the application of an eddy‐tracking algorithm, a spatial and temporal analysis of a variety of factors that impact mixed layer variability, and a heat budget analysis that there is an overall dominance of larger features in strong monsoon conditions and a higher frequency of small features in weak monsoon conditions. Key Points: For the first time, we have investigated the impact of mesoscale features on mixed layer variability in the Arabian Sea The eddy field in the strong (weak) monsoon seasons favors larger‐mesoscale (smaller‐mesoscale) activity Anticyclonic eddies in the Arabian Sea have larger radii and smaller amplitudes for much of the summer monsoon season